Manipulation of the terahertz leaky wave by metal–dielectric–metal metasurface. (20th June 2019) - Cheng, Qingqing; Zhang, Chaoshi; Yu, Dong; Chen, Lin; Xie, Jingya; Zang, Xiaofei; Shkurinov, Alexander; Zhu, Yiming; Zhuang, Songlin
Abstract: We experimentally demonstrated the properties of leaky waves generated inside the air gap between a high-index prism and a metal–dielectric–metal metasurface can be strongly engineered by the geometrical parameters of the metasurface. In particular, we further identified that the excited leaky waves undergo a transition from an over-coupled state to an under-coupled state along with the variation of structure parameters, manifest in their strongly engineered optical responses. These experimental findings can be well explained by the coupled-mode theory, and may have potential implementation in sensitive sensors and detections based on leaky waves.